Assessing the Diet Quality and Nutritional Risk of Pregnant Women in a Tertiary Care Hospital Based on FIGO Nutritional Checklist: A Cross-Sectional Study - Prithika, Prithika; Preethi. B, Preethi. B (Journal of Neonatal Surgery, 2025)
Background: The FIGO (International Federation of Gynaecology and Obstetrics) Nutrition Checklist for Antenatal Care offers evidence-based recommendations to guide healthcare providers and patients in maintaining optimal nutrition throughout pregnancy. Materials and Method: Observational cross-sectional study conducted over 3 months at Sree Balaji Medical College, Chennai, among 215 pregnant women Results: Mean gestational age was 21.6 (SD 7.65) weeks, and mean maternal age was 26.15 (SD 5.98) years. Significant associations were found between FIGO diet standards for fish intake, dairy product intake, whole grain intake, and folic acid intake with hemoglobin levels (p<0.05). Conclusion: The FIGO Nutrition Checklist provides a quick and cost-effective intervention to help healthcare providers manage pregnant women’s nutrition, supporting the health of women and future generations.